The Effect of Tooth Pain Relief Material Scrapbook on The Knowledge and Behavior Criteria of Preventing Tooth Cales for Students of Public Elementary School Cilandak Timur 03 South Jakarta - Pudentiana RE; Siti Nurbayani Tauchid; Erwin Erwin; Nita Noviani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This study aimed to determine the effect of scrapbook media on the knowledge and behavior criteria of students before and after the dental health learning process. This type of research is quantitative research with experimental methods used is quasi-experimental or quasi-experimental with the nonequivalent pretest-posttest control design groups. The population in this study were fourth-grade students at State Elementary School 05 Cilandak Timur, South Jakarta. The sample is a small part of the population that is taken according to certain procedures to represent the population. In this study, the researcher used a Stratified Random Sampling type random sampling technique which the researcher carried out to produce a sample of 4th-grade students in the morning and IV in the afternoon with state school status. The results were that the fourth-grade students from Public Elementary School 05 Cilandak Timur were the control class, while the fourth-grade students from Public Elementary School 03 were the treatment class. In this study, the instrument used was a test sheet in the form of multiple-choice questions to assess the knowledge criteria consisting of 25 multiple-choice questions regarding dental health. The grid of knowledge test instruments includes C4 (Analyzing) to C6 (Creating). Data collection techniques used are pre-test and post-test. The data analysis technique in this study used descriptive statistical analysis, prerequisite test analysis, and inferential statistical analysis.